(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze the effect of the Game-Based Training (GBT) approach on improving students’ basic skills and handball playing skills in extracurricular activities. The research method used a quantitative approach with a Pretest–Posttest Control Group experimental design, involving 20 students who were all sampled using total sampling techniques and randomly divided into experimental and control groups. The research instruments included handball basic skills tests (passing, catching, dribbling, shooting) and playing skills tests using the Game Performance Assessment Instrument (GPAI). The results showed that the experimental group experienced a much more significant improvement than the control group; on the variable of basic handball skills, a t-test value of Sig. 0.000 was obtained with an average increase of 22.4 points, while on playing skills (GPAI), there was also a significant difference between the groups with a value of Sig. 0.000 and an average increase of 13.8 points. These findings indicate that Game-Based Training is effective in improving students’ technical abilities and playing performance in handball. Thus, GBT is suitable to be applied as a training model to improve handball skills in schools.